Syntheses of novel pyridine-based low-molecular-weight luminogens possessing aggregation-induced emission enhancement (AIEE) properties - Hagimori, Masayori; Yoshida, Tatsusada; Nishimura, Yasuhisa; Ogawa, Yukiko; Tanaka, Keitaro (Beilstein Journal of Organic Chemistry, 2022)
Novel pyridine-based fluorescing compounds, viz. pyrido[1,2-a]pyrrolo[3,4-d]pyrimidines 3a,b and N-methyl-4-((pyridin-2-yl)amino)maleimides 4a–e, were selectively prepared by a one-pot reaction between a functionalized maleimide and 2-aminopyridines with electron-donating or electron-withdrawing groups at position 5 and were investigated photophysically and computationally. The photophysical studies revealed that all the synthesized compounds exhibited fluorescence in organic solvents, while N-methyl-4-((pyridin-2-yl)amino)-substituted maleimide derivatives 4a–e, which are based on an acceptor–donor–acceptor (A–D–A) system, exhibited aggregation-induced emission enhancement (AIEE) properties in aqueous media. Compounds 4a and 4e, bearing electron-withdrawing groups (Br and CF3, respectively) showed 7.0 and 15 times fluorescence enhancement. Time-dependent density functional theory (TD-DFT) calculations were performed to gain better insight into the electronic nature of the compounds with and without AIEE properties.
Keywords: acceptor–donor–acceptor; AIEE; low molecular weight; one-pot reaction; ((pyridin-2-yl)amino)maleimide; TD-DFT calculation